VACCINE PREVENTABLE DISEASES IN THE XXI CENTURY - Pírez, Maria Catalina (Journal of Postgraduate Medical Institute, 2012)
All over the world, both in developing and developed countries there are public health authorities and other organizations that are making the best effort to reduce morbidity and mortality of children due to vaccine preventable diseases. At this moment this is mandatory in many countries because by reducing morbidity and mortality, vaccination can contribute substantially to achieve the Millennium Development Goal of reducing the mortality rate among children under five years by two thirds between 1990 and 2015. The vaccination is one of the most cost-effective strategies to control infectious diseases, even at this moment when new and more expensive vaccines are needed. Pneumonia3, neonatal severe infections (most of them pneumonia), measles4, diarrheal disease, neonatal tetanus and meningitis represent the most frequent vaccine preventable diseases.